ANALISIS PENGARUH KEBIJAKAN PENGURANGAN STIMULUS MONETER (TAPERING OFF) AMERIKA SERIKAT TERHADAP KEBIJAKAN MONETER INDONESIA TAHUN 2013-2015 - Nandaputra, M Real Afif; ", Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is a economic political study which describes influence of tapering off of american policy toward change of monetary policy of indonesia. This research will focus on what is the effect of tapering off to Indonesia. This study interesting because describe about a policy of super economic country can make influence to another country. America is the biggest economy in the world. Every policy that they make can influence every country in the world.This is qualitative research which used descriptive methods, and collecting datas from some resources like book , journals, official publications and relevant websites. This paper used the neoliberalism perspective and Monetary Contractive Theory from Nopirin. The object in this research is America and Indonesia.The result of this research shows that the monetary policy of America made some country must change their policy. amerika issued a quantitative easing policy to save the country's economy. the policy is successful and then proceeded to issue the policy tapering off. This second American policy causes Indonesia to experience economic turmoil. to overcome it, Indonesia issued a monetary policy to stabilize its economy again.Keywords : Policy, Monetary, Quantitave easing, Tapering off.